Clinical relevance of IgE-mediated sensitization against the mould Alternaria alternata in children with asthma. (January 2017) - Lehmann, Sylvia; Sprünken, Anja; Wagner, Norbert; Tenbrock, Klaus; Ott, Hagen
Background: Asthma in childhood has a prevalence of 5–10% in Germany and severe asthma accounts for about 5% in this patient group. Positive predictive values for severe asthma are atopy, a positive family history and sensitizations against inhalative allergens. Alternaria is an important inhalative allergen and sensitization is suspected to correlate with severe and lethal asthma. We investigated the prevalence and impact of Alternaria sensitization in paediatric asthma. Methods: We reviewed paediatric patients with a diagnosis of low-grade, moderate and severe asthma. Data collection included concomitant atopic diseases, sensitization profiles, family history and prior hospitalization for asthma exacerbation. Results: A total of 207 paediatric patients (aged 1–17 years) were included in the study. Overall, 25% had low-grade asthma, 31% moderate and 44% severe asthma and 26% were formerly hospitalized. Alternaria sensitization was the most common in moulds, although without significant correlation with hospitalization and severe asthma. Alternaria sensitization increased with age and was significantly associated with co-sensitization against other moulds, grass pollen and cat epithelia. Allergic rhinitis was significantly correlated with hospitalization, independent of Alternaria sensitization. Conclusions: Alternaria sensitization was common and increased with age. No significant correlation was found between asthma degree, hospitalization rates and sensitization profiles. Alternaria sensitization demonstrated no isolated risk factor for severe asthma and hospitalization.